Ethnobotany of Buldhana District (Maharashtra: India): Plants Used in Veterinary Medicine - Aher, Y.A.Dushing, D.A.Patil*, P.S.Patil, Y.A.Ahirrao, U.P. (Journal of Phytology, 2011)
The present paper deals with plants used in veterinary medicine in Buldhana district, which is situated in the northern part of Maharashtra (India). The folk knowledge about medicinal plants is still prevalent in the region. The increasing force of acculturation in the area indicated urgency in recording such data. A field study was carried out during 2006-2009. It was aimed at documentation, analysis and assessment of ethnobotanical knowledge in the study area. We performed structural interviews as well as open discussions with about 5-8 informants (with age between 50-65). It is compared with literature available to date. Eighty plant species belonging to 44 families have been reported as employed by the rural folks and tribals. A list of a plant species alongwith their family, local name, plant part/s used, medicinal recipe and mode of administration for effective control of different ailments. These remedies are mostly extended for cows, calves, bullocks, buffaloes, goats and sheeps. The main ailments treated are wounds, bone fractures, stomach and gynecological complaints. In few cases, the use of these remedies is also consistent with their use in human medicine. These are also discussed from the standpoint of ‘doctrine of signatures’. Buldhana district has a rich repository of medicinal plants and this reinforces the need for concomitant evaluation of their chemical contents and biological activity as a basis for developing future medicines. Key words: Ethnobotany; Buldhana district; Maharashtra; Ethnoveterinary; Traditional knowledge <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">D.A.Patil edited. Ethnobotany of Buldhana District (Maharashtra: India): Plants Used in Veterinary Medicine. J Phytol 2/12 (2010) 22-34.